An Integral Method of Environmental Design for identifying habitability factors. An approach from a socio-environmental baseline (2014)
The article proposes the Environmental Design Integral Method of Environmental Design (MIDA, in Spanish) to enhance the conditions for habitability in urban and architectural projects. It explains how MIDA broadens the traditional recognition of the site of study by taking into account social variables and indicators such as population, density and quality of public utilities in the immediate context of the area of analysis, as well as geographical position, environmental factors and basic sanitation at an ecological level. It then focuses on how these variables break down into subvariables allowing for a detailed and holistic approach in research and design processes in architectural fields, and illustrates the application of the MIDA in Bogota. It concludes that MIDA contributes positively to lay down socio environmental comfort standards and to provide reliable data and strategic design variables, suitables to architects and urban planners when determining optimal habitability parameters for their projects.